Probabilistic Neutron Tracker - Trulsson, Linus; Törnqvist, Hans (My University, 2009)
In order to gain further understanding of subatomic physics, research is conducted close to the drip line, where the ratio of the constituents of the nuclear core is at the extreme. In experiments, liberated neutrons, which have no charge, are difficult to detect because only the effects of collisions with charged particles can be observed. Collisions at the subatomic level may involve different physical processes and branch into several other collisions. A neutron detector called LAND, situated in the GSI facility outside Darmstadt, Germany, is capable of observing these collisions. The algorithm currently used to recognize neutrons from the collisions is heavily based on macroscopic observations of how the neutron detector behaves. It is greedy and therefore tends to underestimate the number of neutrons for complicated events. This project continues investigations from an earlier project, aimed at de- signing a probabilistic method to reconstruct neutrons from neutron detector data. Visualisations of the new algorithm show promising results of resolving neutron paths and branching and statistical results show good capabilities in estimating the number of neutrons. Some very important problems could not be solved, but the effects of the problems can be understood and explained from the obtained results. An algorithm based on probability functions of subatomic interactions seems to be a viable concept and will most probably see continued exploration and improvement by future masters students.
Keywords: Mellanenergifysik; Grundläggande vetenskaper; Fysik; Acceleratorfysik och instrumentering; Middle energy physics; Basic Sciences; Physical Sciences; Accelerator Physics and Instrumentation